RESISTENSI ANTIBIOTIK DAN STRATEGI FARMAKOLOGIS TERBARU: INTEGRASI BUKTI GLOBAL DAN LOKAL - dewi mega, dewi (Institut Teknologi dan Kesehatan Bintang Persada, 2026)
Antimicrobial resistance (AMR) continues to be a global threat, especially in nosocomial infections that are increasingly difficult to treat. This study summarizes findings from ten international and national journals discussing various aspects of antibiotic resistance from 2020 to 2025, covering the prevalence of multidrug-resistant pathogens, the rationality of antibiotic use, and future therapeutic innovations. In China, resistance in hospital-acquired infections shows an increasing trend, particularly in Pseudomonas aeruginosa and Acinetobacter baumannii. Corynebacterium striatum has also been reported as an emerging invasive pathogen with a global increase in cases since 1976. In Indonesia, local studies have noted the high prevalence of multidrug-resistant Klebsiella pneumoniae and the misuse of empirical antibiotics not based on pharmacokinetics. Additionally, the use of nebulized antibiotics shows potential for preventing Gram-negative infections in critically ill patients. Innovative therapeutic approaches, including new-generation antibiotics based on biotechnology such as CRISPR and phage therapy, show potential in combating resistance. Resistance control programs, such as routine antibiogram evaluation and healthcare worker education, are key to mitigation efforts. This review emphasizes the need for integration between clinical, microbiological, and pharmacological policy approaches to sustainably control antibiotic resistance. By combining global and national data, this article provides a comprehensive overview of the current landscape of antibiotic resistance and the prospects for more specific, adaptive, and rational therapies in the future.